How a patient-led advocacy organization supports the road to diagnosis and treatment of creatine transporter deficiency - Wallis, Heidi; Iyer, Sangeetha; Reinhardt, Emily K. (Frontiers in Neuroscience, 2025)
The current era of drug development has evolved significantly. Patient advocacy organizations are moving beyond simply supporting community members and are taking the reins to improve the speed of diagnoses, initiate therapeutic discoveries, and lay the groundwork to ensure successful clinical trials. The Association for Creatine Deficiencies (ACD) is an international parent-led patient advocacy organization focused on the three ultra-rare neurodevelopmental monogenic disorders resulting in Cerebral Creatine Deficiency Syndromes (CCDS). These include X-linked creatine transporter deficiency (CTD), guanidinoacetate methyltransferase (GAMT) deficiency, and l-arginine:glycine amidinotransferase (AGAT) deficiency. While each is rare in its own right, the unified CCDS community is effectively advancing the field of CCDS with each disorder benefiting from progress made in the other two disease areas. ACD collaborators include caregivers, academic researchers, clinicians, industry partners, and policymakers. Since its founding in 2012, the organization has evolved and achieved significant milestones. These include advancements in disease diagnosis, investments in various therapeutic modalities, creation of a collaborative research community, a unified patient community contributing essential patient data, and repositories of patient-derived specimens. The initiatives of ACD are intended to create the earliest diagnosis possible through newborn screening, to have an effective treatment, and to make disease management strategies available to all members of the CCDS community, including those diagnosed at later stages and experiencing greater effects of the diseases.